A REPORT OF THE COMMITTEE ON AUDITING EDUCATION. - Major, John E.; Matthies, William R.; Niswonger, C. Rollin; Peacock, Erle E.; Miller, Herbert E. (The Accounting Review, 1954)
Abstract The article presents the report of the Committee on Auditing Education appointed by the American Accounting Association. The concern of the committee was to secure an evaluation of the job the colleges are doing in preparing students for public accounting. The committee solicited the opinions of public accountants along the above lines by the use of a questionnaire which was mailed to 98 local firms and ten national firms. Responses were received from 57 per cent of the local firms and from all of the national firms. The questionnaire invited an expression of opinion regarding which objective colleges should adopt in preparing students for the public accounting profession. Poor English and lack of ability to write and speak effectively are the most serious of the weakness of college graduates reported by the public accountants. The public accountants believe that such weaknesses can be corrected by requiring accounting students to take more courses in grammar and public speaking slanted to the interests of accountants.